Pengaruh Budaya Kerja Terhadap Pelaksanaan Pelatihan Aplikasi Sistem Keuangan Desa (SISKEUDES) oleh Dinas Pemberdayaan Masyarakat dan Kampung Kabupaten Aceh Singkil - Hasanah, Fenni; Frinaldi, Aldri (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research is based on the problems of work culture on the implementation of siskeudes training by the department of community empowerment and the village Aceh Singkil district. The purpose of this study is to analyze the effect of work culture on the implementation of the siskeudes training. The method used is a quantitative method with the type of associative research. The sampling technique used was the proportionate stratified random sampling technique. This quantitative research used a Likert scale questionnaire which was used to test its validity and relevance. From the population, the researcher got 121 people as a total sample. This research shows the positive impact that occurs in work culture on the implementation of siskeudes training towards the department of community empowerment and the village Aceh Singkil district, this can be seen from the significance value which is 0.000 less than 0.05 and the percentage of contribution from variable X to Y is 42.2%. It is known from the results of this research that a good work culture can deliver an improvement in the implementation of siskeudes.